ANALISIS TERHADAP DESAIN INDUSTRI PADA KEMASAN MAKANAN GEPREK BENSU (STUDI KASUS PUTUSAN NOMOR 16/PDT. SUS-DESAIN INDUSTRI/2020/PN NIAGA. JKT.PST. JO. PUTUSAN NOMOR 162 K/PDT.SUS-HKI/2021): Juridicial Analysis of Industrial Design on Geprek Bensu Food Packaging (Case Study of Verdict Number 16/Pdt. Sus-Desain Industri/2020/PN Niaga.Jkt.Pst. jo. Verdict Number 162 K/Pdt.Sus-HKI/2021) - Keren Aras Hana; Simona Bustani (AMICUS CURIAE, 2025)
Law Number 31 of 2000 on Industrial Designs mandates the registration of an Industrial Design to obtain legal rights over it. In the industrial design dispute between Ruben Samuel Onsu and Benny Sujono, the protection of Ruben Samuel Onsu’s Industrial Design failed due to issues regarding its novelty, although the design was successfully registered. This research is normative juridical and descriptive-analytical in nature, using secondary data comprising primary and secondary legal materials through literature study. The data were processed qualitatively and conclusions were drawn deductively. The identified problem in this study is the suboptimal legal protection of industrial designs due to the absence of a mandatory and permanent substantive examination mechanism. Based on the results and conclusion of the study, it is concluded that Benny Sujono does not have sufficient legal interest to request the cancellation of the industrial design right, as the legal interest under Article 38 of the Industrial Design Law encompasses not only economic interest but also personal interest recognized by law. Decision No.16/Pdt.Sus-Desain Industri/2020/PN Niaga.Jkt.Pst. jo. Decision No.162 K/Pdt.Sus-HKI/2021 does not fully reflect the provisions of the Industrial Design Law, particularly regarding novelty examination, thus requiring further regulation on mandatory substantive examination and clarification of ambiguous terminology in industrial design law.